Germany’s Green Hydrogen Transition: Ambitions, Realities and Economic Barriers - Fatima, Hadji; Wafa, Chemani; Achour, Sadok; Rimi, Okba; Tir, Abdelhak (Journal of Ecohumanism, 2025)
Green hydrogen is a key component of Germany’s strategy for a sustainable energy transition, which aims to significantly reduce carbon emissions by 2050. Germany relies heavily on it as a fundamental part of its energy transformation and has set ambitious targets for its production and imports. However, despite progress in green hydrogen production, gray hydrogen remains dominant in German industry, reflecting the economic and technological challenges Germany faces in this area. Among the most significant challenges are the high cost of green hydrogen compared to other hydrogen types and the lack of a sophisticated infrastructure for its distribution and storage. Nevertheless, Germany is striving to expand the use of green hydrogen by investing in numerous projects and supporting research and development in electrolysis technologies.